2018
DOI: 10.3389/fimmu.2018.02353
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Systemic and Parasite—Antigen Stimulated Levels of Type III IFNs in a Chronic Helminth Infection and Reversal Following Anthelmintic Treatment

Abstract: Type III IFNs are important players in immunity to viral and bacterial infections. However, their association with helminth infections has not been examined. To explore the association of Type III IFNs with Strongyloides stercoralis (Ss) infection, we examined the systemic levels of IFN lambda-1, IFN lambda-2 and IFN lambda-3, IL-10, and CXCL10/IP-10 in Ss infected (INF, n = 44), helminth—uninfected (UN, n = 44) and in post-treatment INF individuals. We also examined the levels of IFN lambda-1, IFN lambda-2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The results of our study are similar to other related studies, but there are also some differences: some studies have shown that the protective effect of helminth infection is transient and can be reversed by anthelmintic treatment 28,29 . The possible reason is that they researched soil‐transmitted helminths (STHs) infections, but we researched Schistosomiasis japonica infections.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of our study are similar to other related studies, but there are also some differences: some studies have shown that the protective effect of helminth infection is transient and can be reversed by anthelmintic treatment 28,29 . The possible reason is that they researched soil‐transmitted helminths (STHs) infections, but we researched Schistosomiasis japonica infections.…”
Section: Discussionsupporting
confidence: 83%
“…Other evidence suggests that soil‐transmitted helminth (STH) infections are associated with lower insulin resistance (IR), but deworming programmes might remove this helminth‐associated protective effect 28 . Strongyloides stercoralis (Ss) infection is directly associated with increased parasite antigen stimulated levels of type III IFNs since anthelmintic treatment and presumed cure result in a significant reversal in the systemic levels of type III IFNs 29 …”
Section: Discussionmentioning
confidence: 99%
“…We wanted to examine the Type1 and Type III IFN kinetics following RT-PCR confirmation from days 15-30 to more than 180 days. To this end, we combined all the groups irrespective of their disease status (mild, moderate, severe and convalescence) [12][13][14][15].…”
Section: Study Population Characteristicsmentioning
confidence: 99%
“…Acute COVID-19 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) 151-180, n = 37 and more than 180, n = 40), residing in Chennai and Tiruvallur were enrolled in the study between November 2020 and December 2020 after taking informed consent from the study individuals. This was a cross-sectional study and different individuals were enrolled in the different categories.…”
Section: Study Populationmentioning
confidence: 99%
“…In contrast, a recent report suggested that pDC accumulation in the lung during viral infection facilitates type 2 allergic airway exacerbations in an OVA-driven model, with Ab-mediated depletion of pDCs reducing type 2 cytokines in the draining LNs (dLNs) (28). In humans, along with cDCs, pDC numbers in the blood are increased during infection with the soil-transmitted nematode Strongyloides stercoralis, compared with numbers in endemic healthy and anthelmintictreated individuals (29). We previously demonstrated that unlike reports from allergic airway models, negative regulation of type 2 inflammation is not a hallmark pDC function in the early stages of S. mansoni infection (6).…”
Section: Introductionmentioning
confidence: 96%